Case Report: Case series: association between blood concentration and side effects of sotorasib - Shigaki, Ryota; Yoshida, Ryohei; Yagita, Akari; Nagasue, Kazunori; Naraoka, Taeka; Nitanai, Kiichi; Yanada, Hiraku; Tenma, Toshiyuki; Kida, Ryotaro; Umekage, Yasuhiro; Mori, Chie; Minami, Yoshinori; et al. (Frontiers in Oncology, 2023)
Introduction Sotorasib is a crucial therapeutic agent for patients with non-small cell lung cancer (NSCLC) harboring the KRAS p.G12C mutation. Despite its efficacy, the relationship between blood sotorasib concentrations and side effects remains largely unexplored. Methods This study enrolled five patients with KRAS p.G12C-positive NSCLC treated with sotorasib (LUMAKRAS® Tablets, Amgen, Japan) between July 2022 and February 2023 at Asahikawa Medical University Hospital. Blood sotorasib levels were monitored, and their association with adverse events was examined, with no adjustments made to drug dosages based on these levels. Results Variable blood sotorasib levels were observed among the participants. Notably, one patient developed interstitial pneumonitis, although a definitive attribution to sotorasib was uncertain due to prior pembrolizumab treatment. The study revealed no consistent association between blood sotorasib levels and adverse events or therapeutic outcomes, with some patients experiencing severe side effects at higher concentrations, while others did not. Conclusion Preliminary findings suggested that monitoring blood sotorasib levels may aid in anticipating adverse events in this small cohort. However, future studies with larger sample sizes and extended follow-up periods are required to validate these initial observations. Such studies could potentially offer insights into personalized dosing strategies, thereby mitigating adverse effects and enhance patient care for individuals with KRAS p.G12C-positive NSCLC.